Synthesis, characterization, and electrochemical and in-situ spectroelectrochemical properties of novel peripherally and non-peripherally 7-oxy-3-(3,4-dimethoxyphenyl) coumarin substituted phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; SALAN, ÜMİT (ELSEVIER SCI LTD, 2019)
Novel metal-free (4 and 9), Zn(II) (5 and 10) and Co(II) (6 and 11) phthalocyanines (Pcs) bearing four 7-oxy-3(3,4-dimethoxyphenyl)coumarin (1) substituents at peripheral (13) and non-peripheral (a) positions have been prepared by cyclotetramerization reactions of 4-(3-(3,4-dimethoxyphenyl)coumarin-7-oxy)phthalonitrile (3) or 3-(3-(3,4-dimethoxy-phenyl)coumarin-7-oxy)phthalonitrile (8), respectively, in the presence of relevant metal acetate salts in N,N-dimethylaminoethanol. The compounds have been characterized by elemental analysis, FTIR, UV-Vis and MALDI-TOF mass spectroscopies. Thermal properties of the compounds were evaluated by thermogravimetric analysis and differential scanning calorimetry. Electrochemical redox properties of all compounds were investigated by voltammetric and in-situ spectroelectrochemical measurements in dimethylsulfoxide including tetrabutyl ammonium perchlorate as the supporting electrolyte. The metal-free and Zn(II)Pc compounds displayed Pc ring-based redox processes whereas both Pc ring-based and metal-based electron transfer processes were observed for Co(II)Pc complexes. H-aggregation tendency of peripherally substituted compounds was found to be much higher than that of non-peripherally substituted ones. It was observed that there have been systemmatic redox potential and aggregation behaviour differences between the peripherally and non-peripherally substituted Pc compounds. These differences were attributed to different sterical and conformational effects of these substitution patterns. In-situ spectroelectrochemical and in-situ electrocolorimetric measurements suggested that peripherally substituted Co(II)Pc is a multi-coloured chromophore material displaying distinct spectral and colour changes during the first reduction and oxidation processes, and thus, being suitable for electrochromic applications.
Keywords: Phthalocyanine; Coumarin; Synthesis; Aggregation; Electrochemistry; BALL-TYPE PHTHALOCYANINES; GAS-SENSING PROPERTIES; METAL-FREE; INDIUM(III) PHTHALOCYANINES; LU(III) PHTHALOCYANINES; COBALT PHTHALOCYANINES; PHOTODYNAMIC THERAPY; OXYGEN REDUCTION; BEARING COUMARIN; OXIDATION